5.1k views
4 votes
Evaluate.



6^2+(3⋅4)−2^4

User Georgexsh
by
4.7k points

2 Answers

2 votes

Answer:

32

Explanation:


6^(2)+(3⋅4)−
2^(4)


6^(2)+(12)-
2^(4)

(
6^(2)=6x6=36)

36+12-
2^(4)

(
2^(4)=2x2x2x2=16)

36+12-16

48-16

32

use the order of PEMDAS

P parentheses

E exponents

M Multiplication

D division

A addition

S subtraction

User Harvard
by
5.6k points
0 votes

Answer:

Explanation:

First you want to do what is in the paratheses which is 3*2 which equals 6

Next do the multiplication and division left to rightwhich is 6*2 which equals 12 and 2*4 which equals 8

Last do your addition and subtraction left to right

12+12-8=16

User Amateur
by
4.9k points